Spatial distribution of teenage pregnancy and its associated factors in Ethiopia: spatial and multilevel analysis of EDHS 2019 - Meron Asmamaw Alemayehu; Atalay Liknaw Birhanie; Moges Tadesse Abebe; Werkneh Melkie Tilahun; Worku Necho Asferie; Anteneh Kassa Yalew; Muluken Chanie Agimas; Tigabu Kidie Tesfie; Mekuriaw Nibret Aweke; Fantu Mamo Aragaw (BMC, 2024)
Abstract Background One of the reasons for the high rates of maternal and child morbidity and mortality in Sub-Saharan Africa is the rising proportion of teenage pregnancy. Preventing teenage pregnancy is critical to meeting sustainable development goal number three which aims to reduce the global maternal mortality ratio to less than 70 per 100,000 live births. To support the achievement of this goal, this study aimed to assess the spatial variation and factors associated with teenage pregnancy in Ethiopia using the recent nationally representative data. Methods A secondary data analysis of the 2019 Ethiopian mini Demographic and Health Survey was conducted with a total weighted sample of 2211 (unweighted 2100) teenagers. The Bernoulli model was fitted using SaTScan version 9.6 to identify hotspot areas and the geospatial pattern and prediction of teenage pregnancy were mapped using ArcGIS version 10.7. A multilevel logistic regression model was fitted to identify factors associated with teenage pregnancy among teenagers. Adjusted OR with 95% CI was calculated and variables having a p-value less than 0.05 were statistically significant factors of teenage pregnancy. Result The prevalence of teenage pregnancy among adolescents aged 15-19 years in Ethiopia was 12.89% (95% CI: 11.56%, 14.36%). The SaTScan analysis identified a primary cluster in the Gambella region of Ethiopia (log-likelihood ratio = 14.02, p < 0.001). A high prevalence of teenage pregnancy was observed in Somalia, Afar, Gambella, and the southern part of the Oromia regions of Ethiopia. Age, educational status- primary and secondary, religion- protestant, having television, contraceptive knowledge, household head-female, and region- Small peripheral were significant determinants of teenage pregnancy. Conclusion The spatial distribution of teenage pregnancy in Ethiopia was nonrandom. Age, educational status, religion, having television, contraceptive knowledge, sex of household head, and region were significant determinants of teenage pregnancy. Therefore, concerned government bodies and other stakeholders should organize periodic educational campaigns and youth-friendly reproductive health services. Collaboration between healthcare professionals, and religious and community leaders could also form a strategic partnership that makes interventions more comprehensive, culturally sensitive, and effective in reducing teenage pregnancy.